A successful audit with multidisciplinary intervention in controlling hospital acquired infections in postpartum mothers in a Tertiary Care Obstetrics Unit - Chinniah, T.R.; Senanayake, H.; Bandara, K.C.; Alles, M.F.; Kahandawaarachchi, I. (Elsevier, 2015)
Purpose: Hospital acquired infection (HAI) in obstetrics is an important component of expenditure in health sector and delays discharge of patient and bonding of mother with baby. A retrospective study done for 12 months in an obstetric unit revealed 32/810(4%), 3/78(4%), 28/131(21%), 3/12(25%) and 3/27(11%) following normal vaginal delivery (NVD), elective lower section cesarean section (LSCS), emergency LSCS, forceps delivery and vacuum delivery respectively, had a prolonged stay due to clinically suspected and/or laboratory proven infections. Methods: These results were made aware to stakeholders; various interventions were done to promote strict infection control measures during these procedures. Following these, a prospective study was carried out in the same obstetric unit, over a period of 6 months, adhering to same criteria as of the previous study. All pregnant mothers with uneventful antenatal history were included into the study. Prolonged stay was defined as stay over 24 hours following normal /assisted vaginal delivery and 3 days following LSCS. Any clinically suspected and/or laboratory proven infections were considered as HAI. Results: 12/739(1.6%) and 2/93(2.1%) following NVD and Emergency LSCS respectively, had prolonged hospital stay due to clinically suspected and/or laboratory proven infections. Pregnant mothers who underwent elective LSCS, forceps or vacuum deliveries did not have HAI following these procedures. Average prolonged stay due to HAI following NVD and emergency LSCS were 4.5 days and 6.5 days respectively. Conclusions: Following interventions to promote strict infection control measures during procedures of delivery, a statistically significant ...
Keywords: Hospital acquired infection; normal vaginal delivery; lower section cesarean section